Prevalence of risk for eating disorder amongst International Islamic University Malaysia medical students and its associated factors - Pasi, Hafizah; Mohd. Rus, Razman; Ab Rahman, Jamalludin; Abd. Aziz, Karimah Hanim; Nasreen, Hashima E; Swe, Swe Latt (2015)
Introduction: Eating disorders are a poorly understood condition characterised by severe psychiatric and medical manifestations, in which eating habits, physical health and psychosocial functioning are disturbed. College and university students are among the population who are prone to eating disorder. The aim of this study is to determine the prevalence of eating disorders risk in the International Islamic University Malaysia (IIUM), Kuantan campus amongst the medical students and to identify its associated factors. Materials and Methods: A cross sectional study involving 200 medical students of IIUM Kuantan campus session 2014/2015 of all years (20-26 years old) of both genders using a self-administered questionnaire through an online website which is a Google drive between 29th June till 10th July 2015. Result: This study revealed that the prevalence of risk for eating disorder among IIUM Kuantan campus medical students is 15.0 percent. On the same note, the risk is noted to be higher among single female of Malay ethnicity, being middle child, overweight and physically inactive; albeit none of these factors significantly associated with risk of eating disorder among this population. Conclusion: The prevalence of those who have the risk of eating disorder in this study is comparable to the result from the previous studies conducted among college and university students in Malaysia. Nevertheless, the risk of eating disorder is documented among IIUM medical students and warrant a closer look and appropriate reference for those who have the risk.